ORAL MANIFESTATIONS IN PATIENTS WITH CYSTIC FIBROSIS - Mădălina Andreea Donos; Laura Otilia Boca; Elena Țarcă; Lorena Mihaela Manole; Otilia Elena Frăsinariu; Laura Mihaela Trandafir (Romanian Society of Oral Rehabilitation, 2022)
Objective: The purpose of this paper is to review literature data related to oral manifestations in patients with cystic fibrosis and to emphasize the importance of prevention and early identification, as much as possible, of these manifestations in order to increase the patients' quality of life. Materials and method: Articles published in international indexed databases were evaluated, mostly from PubMed, using the following search terms: cystic fibrosis, oral manifestations, dental, periodontal, enamel, caries, in combination with several synonyms such as teeth, oral cavity, oral mucosa, periodontitis, carious lesions. Results: Patients with cystic fibrosis have numerous modifications in the composition and proprieties of saliva which lower resistance to microorganisms. Studies showed higher prevalence of enamel disorders in permanent dentition, and enamel hypoplasia was the most frequent defect. On the other hand, data regarding carious lesions showed a lower risk of occurrence at patients with cystic fibrosis compared to control group. Conclusions: Stomatologists should be part of cystic fibrosis multidisciplinary team, as the oral modifications are frequent at the patients diagnosed with this disorder.